Improving Patient Experience through Meaningful Engagement: The Oral Health Patient's Journey - Shamiso Chakaipa; Sarah J. Prior; Sue Pearson; Pieter J. van Dam (MDPI AG, 2023)
Healthcare organisations around the world have embraced the valuable role that patient experience plays in the improvement of health care delivery. Engaging with patients is a vital component of understanding how to deliver safe, high-quality, respectful health care that is person-centred and efficient. In oral health services, patient experience is historically predominantly reported as challenging, which is most commonly associated with past traumatic experience with poor oral health treatment. Additionally, the high out-of-pocket costs associated with oral health treatment can mean that people disengage with these services, thereby worsening their oral health conditions. Consequently, oral health has an enormous task to reduce the negative perceptions and experiences. This demands innovative and subtle ways to navigate and address patient and service challenges. Exploring and acknowledging the myriad of historical challenges that exist for oral health patients and utilising these experiences to support change will ensure person-centred improvements are designed and implemented. Therefore, this perspective paper defines patient experience and proposes how oral health patient experience can be improved using the concept of meaningful engagement with a focus on the Australian context. We identified two important concepts that impact oral health patient experience and explored how these concepts may play a role in improving oral health services through improved patient experience. The first concept is person, patient, and user which focusses on general patient experience journey in a general health care setting. The second concept is preservice, current service, and post service which relates to an oral health patient's experience journey in an oral health service setting. Our findings suggest that the practitioner-patient relationship and use of technology are central to patient engagement to improve patient experience.